Assessment of Sociodemographic Data, Self Mutilation, Suicide Attempt and Psychiatric Disorders in Children and Adolescents who Abused Sexually - Uytun, Merve Çıkılı; Yılmaz, Rabia; Öztop, Didem Behice; Özdemir, Çağlar (The Bulletin of Legal Medicine, 2016)
Objective: It is now generally known that undergoing a sexual abuse may lead to self-destruction, suicide, post-traumatic stress disorder (PTSD), depression and dissociative disorders. Our study aims at determining the rate of self-destruction and suicide among children who had experienced sexual abuse and determining the rates of depression, PTSD and dissociative disorders and their relationships each other.Materials and Methods: The children aged 0-18 who had undergone sexual abuse and sent to Prevention of Child Abuse, Application and Research Center at Erciyes University between 01.01.2011-31.12.2011 to have a judicial report were analyzed retrospectively with regard to their age, sex, frequency of abuse, psychiatric diagnosis according to DSM IV-TR and leaving home or suicide behaviors. The children were made to complete Depression Scale for Children (CDI), Child Post-Traumatic Stress Reaction Index (RPTS-CS) and Dissociation Questionnaire (DIS-Q).Results: 556 cases were included in our research. There was suicide attempt in 24(4,3%) of them, 15 (2,7%) had the behavior of self-mutilation, 6 (1,1%) of them had the idea to commit suicide. In the scales, RPTS-CS was found significant for 33 (5,6%) cases. The score of the DIS-Q was found significant for 8 (1,6%) cases (>2,5). The mean score of the CDI was found significant for 42 (7,3%) cases (>19).Conclusion: It is not only important to follow up closely the children who had experienced sexual abuse and to protect their mental health, but also it is very important to keep them away from being a victim again and prevent to commit suicide and self-mutilation behaviors.
Keywords: child; adolescent; sexual abuse